The COBAS® TaqMan® hepatitis C virus assays: automated systems for accurate and sensitive viral load quantification. (November 2011) - Colucci, Giuseppe; Knobel, Rolf
In recent years, the real time-based TaqMan ® technology has allowed the development of highly sensitive hepatitis viral load tests with broad dynamic ranges. The increasing applications of these tests in clinical diagnostics have shown the utility of viral load as a predictive marker of treatment response and proven its key role in invidualized antiviral therapies. Future refinement in viral load assays, including higher sensitivity, genotype inclusivity, standardization and automation, will further foster the concept of personalized healthcare in the clinical management of chronic hepatitis C.